Teachers' Attempts to Respond to Students' Lived Experiences. Issue 5 (4th July 2021) - Hagenah, Sara; Thompson, Jessica
ABSTRACT: How science teachers attend to key features of teaching scientific phenomena and the overlap with students' lives is the focus of this study. Our conceptual framework is informed by work on resource pedagogies, which examines how teachers build on students' language and stories of their lived experiences as a meaningful way to build content knowledge in a discipline. We examined 38 secondary science teachers' instruction, then purposefully selected 3 teachers who rated highest in being responsive to students' lived experiences in classroom discussions for an in-depth analysis. We observed 1 unit of instruction in each teacher's classroom and conducted interviews to examine teachers' pedagogical reasoning with students' resources. The findings suggest responsive practices teachers used to draw on students' lived experiences when planning and enacting phenomena-based instruction.